Comparison of organic wastewater treatment using anaerobic reactors fixed bed type in Germany and Indonesia - Laras Andria Wardani; Raldi Hendro Koestoer (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2023)
Waste that has a high organic matter content can be treated biologically under anaerobic conditions or using bacteria that can live in an environment without oxygen. One method of wastewater treatment that can reduce high organic content is the Fixed Bed type anaerobic reactor system. The purpose of this research is to compare the treatment of organic wastewater using a Fixed Bed type anaerobic reactor that has been implemented in Germany with that implemented in Indonesia. The method used is a literature study by comparing case studies between the two countries, so the methodology used is a systematic literature review. Based on the results of the discussion, it is known that the organic waste that is processed using an anaerobic reactor carried out in Germany has several differences starting from the sub-stages of the process, and operations to the materials used such as the use of pumps, installation storage tanks, sewage filtration, use of stainless steel and heat exchangers. These differences if applied in Indonesia can cost relatively a lot so they are not suitable for application in Indonesia. Based on the literature study, it was concluded that the anaerobic wastewater treatment solution using a fixed bed type in Indonesia can be a good opportunity and can be imitated by other countries because it has simple equipment, but the reactor efficiency and the resulting percentage of methane production are relatively high. although the required HRT is long, anaerobic catalysts can be used as a solution.